Uji Kombinasi Pupuk Anorganik Dan Pupuk Bio-Organik P Terhadap Ketersediaan P Dalam Tanah, Serapan P Tanaman, Dan Populasi Bakteri Pelarut Fosfat Pada Tanaman Kedelai (Glycine Max L. Merrill): Combination Test of Inorganic Fertilizer and Bio-Organic Fertilizer on P Availability in Soil, Plant P Absorption, and Population of Phosphate Solvent Bacteria in Soybean Plants (Glycine Max L. Merrill). - Baiq Fitri Pebrianti R.P; Lolita Endang Susilowati; Zaenal Arifin; Mansur Mashum; Rika Andriati Sukma Dewi (LPPM Universitas Mataram, 2023)
The application of bio-organic P fertilizer alongside inorganic fertilizers plays a crucial role in increasing available phosphorus (P) for plants while also aiming to reduce and optimize the use of inorganic fertilizers. This combination is expected to enhance crop yields, balance nutrient availability, and improve soil structure. The objective of this research was to investigate the impact of the combination of inorganic and bio-organic P fertilizers on soil P availability, P uptake in soybean plants, and the population of Phosphate-Solubilizing Bacteria (PSB) during the vegetative phase. The research utilized an experimental approach with four treatments. Each treatment involved five randomly selected samples, resulting in a total of 20 experimental units. The study was conducted from March to July 2019 in paddy fields in Semoyang Village, Praya Timur Subdistrict, Central Lombok Regency. The treatments used were as follows: P1 (50% of the recommended inorganic fertilizer + 10 g of bio-organic P fertilizer per plant), P2 (75% of the recommended inorganic fertilizer + 10 g of bio-organic P fertilizer per plant), P3 (100% of the recommended inorganic fertilizer), and the control group (without any treatment). The parameters analyzed in this study were the available P content in the soil, soil pH, dry weight of biomass, P uptake in plants, and the population of Phosphate-Solubilizing Bacteria. The results demonstrated that the treatments involving the combination of inorganic and bio-organic P fertilizers showed improvements in all tested parameters compared to using only inorganic fertilizers. The soil pH ranged from 6.56 to 6.64, available soil P ranged from 13.2 to 17.33 ppm, dry weight of biomass ranged from 8.2 to 11.01 grams, P uptake in plants ranged from 10.69 to 16.76 mg per plant, and the population of PSB ranged from 1.14×106 cfu/g to 4.56×107 cfu/g.